Evaluation of the effects of asymmetric lumbosacral transitional vertebra on pelvic morphology in dogs using ventrodorsal radiographs - Jon Andre Berg; Bente Kristin Saevik; Frode Lingaas; Catrine Trangerud (Acta Veterinaria Scandinavica)
Abstract Background A lumbosacral transitional vertebra (LTV) is a congenital anomaly of the caudal vertebral column. It has been associated with asymmetrical canine hip dysplasia (CHD) and cauda equina syndrome (CES) in German Shepherd dogs. This retrospective cross-sectional study aims to report the potential influence of asymmetric LTV on pelvic anatomy using ventrodorsal (VD) radiographs. Results The results are based on the evaluation of VD radiographs of 13,950 dogs from 14 breeds; an LTV was identified in 18.5%. The LTV segments were allotted into symmetrical (78.6%) and asymmetrical (21.4%) categories. An asymmetrical CHD grade was observed in 12.4% of the dogs, of which 39.7% had asymmetrical LTV. An asymmetric LTV was associated with an uneven sacroiliac joint length, in which the shortest sacroiliac joint is positioned more caudally, resulting in a reduced distance to the hip joint (P < 0.001). Rotation of the asymmetrical LTV segment about the long axis was associated with opposite pelvis rotation vertically (P < 0.001). Also, long-axis rotation of the asymmetric LTV segment was associated with an elevation of the pelvis (P < 0.001), promoting an asymmetrical CHD grade (P < 0.001). Conclusions This study suggests a compensatory mechanism for the sacroiliac joint related to an asymmetrical LTV. Counter-rotation between the pelvis and the LTV segment vertically may straighten the lower back. The asymmetrical LTV segment most likely affects the rotation of the pelvis and may indirectly promote an asymmetrical CHD grade.